Pola Pelayanan Paulus Menurut Kisah Para Rasul - Pangeti, Marhareni (Sekolah Tinggi Teologi Injili Indonesia Palu, 2023)
After receiving the assignment from Jesus to be an apostle to the nations, Paul enthusiastically carried out his assignment. (Rom 11:13) On his first missionary journey, he passed through Cyprus and arrived in Asia Minor. He was driven from various cities by angry mobs, even stoned and abandoned because he was thought to be dead. However, he returned to those cities to strengthen those who had become disciples.